Growth patterns, Mn/Ca values and microstructures in the hinge plate of the studied Arctica islandica . - Nils Höche (10204233); Eric O. Walliser (10204236); Niels J. de Winter (3358778); Rob Witbaard (549727); Bernd R. Schöne (8187015) (2021)
(A) Mutvei-stained hinge plate of specimen Nioz-TC-12-A2R when viewed under a stereomicroscope with sectoral dark-field illumination. LA-ICPMS analysis was conducted prior to the immersion in Mutvei’s solution. Black dashed lines denote annual growth lines. Red solid lines = disturbance lines. These lines reflect handling stress (collection in the Baltic Sea, transferal to NIOZ, transferal to experimental tanks) and delimit the growth band that formed during the 4-week acclimatization phase. (B+C) Magnifications of (A): light microscopy (B) and SEM (C). (B) Portions formed during the acclimatization phase showed faint microgrowth patterns (the most defined ones indicated in yellow) possibly corresponding to circatidal or circalunidian increments and lines. Portion formed in tank was devoid of annual or disturbance lines. (C) Shell microstructures. Shell portions formed in the Baltic Sea consisted predominantly of crossed-acicular (CA) microstructure and exhibited variable sizes of the BMUs. The beginning of the experimental period is marked by a prominent spherulitic prismatic (SphP) disturbance line (red) followed by a zone of fine complex crossed-lamellar (FCCL) microstructure during the acclimatization phase. After another disturbance line, uniform CA microstructure is visible which formed in the experimental aquaria. (D) Ontogenetic changes of shell Mn/Ca ratios. Gray lines denote the different studied specimens; boxplots show distribution of manganese in shell portions formed in nature and during artificial tank environments.